Stwórcze działanie Bożego rûªḥ w Księdze Ezechiela - Pikor, Wojciech (Verbum Vitae, 2020)
The article aims to introduce the theological meaning of the rûªḥ in the Book of Ezekiel. The creative activity of God’s spirit is analyzed first in the prophetic call of Ezekiel (Ezek 1–3) and then in the vision of the Valley of Dry Bones (37:1-14). The same expression rûḥî (“my spirit”) in 36:27; 37:14 and 39:29 not only confirms the creative character of God’s spirit, but reveals its status as a hypostasis of God. The inner renewal – possible through God’s spirit – makes vital the manifestation of God on earth, not only to Ezekiel but also to the Israelites.